Differences in labour market marginalisation among young immigrant groups and Swedish-born youth: Muhammad Ridwanul Amin. (25th October 2022) - Amin, R; Geirsdottir, G; Mittendorfer-Rutz, E; Björkenstam, E; Chen, L; Dorner, T
Abstract: Background: There is a knowledge gap regarding the risk for labour market marginalisation among younger cohorts of refugees and non-refugee immigrants. We investigated if the risk of long-term unemployment (LTU) and disability pension (DP) differs between young refugees and non-refuge immigrants compared to the Swedish-born. The role of age at arrival, duration of residency and morbidity in this association was also investigated. Methods: All 19- to 25-year-olds residing in Sweden on 31 December 2004 (1691 refugees who were unaccompanied by a parent at arrival, 24, 697 accompanied refugees, 18, 762 non-refugee immigrants and 621, 455 Swedish-born individuals) were followed from 2005 to 2016 regarding LTU (>180 days annually) and DP using nationwide register data. Cox regression models were used to estimate crude and multivariate-adjusted (adjusted for several socio-demographic, labour market and health-related covariates) hazard ratios (aHRs) with 95% confidence intervals. Results: Compared to the Swedish-born, all migrant groups had around a 1.8-fold higher risk of LTU (range aHR=1.71-1.83) and around a 30% lower risk of DP (range aHR=0.66-0.76). Older age at arrival was associated with a higher risk of LTU only for non-refugee immigrants. Both older age at arrival and a shorter duration of residency were associated with a lower risk of DP for all migrant groups. Psychiatric morbidity had the strongest effect on subsequent DP, with no significant differences between migrant groups and the Swedish-born (range aHR=5.1-6.1). Conclusions: Young immigrants had a higher risk of LTU and a lower risk of DP than their Swedish-born peers. No differences between the different immigrant groups were found. Age at arrival, psychiatric morbidity and duration of residency are strong determinants of being granted DP. Key messages: Young refugees and non-refugee immigrants both had a similar higher risk of long-term unemployment and a similar lower risk of disability pension than their Swedish-born peers. Age at arrival, psychiatric morbidity and duration of residency are strong determinants of being granted disability pension for young refugees and non-refugee immigrants in Sweden.